Tropical Fowl Mite, Ornithonyssus bursa (Berlese) (Acari: Macronyssidae) - Harold A. Denmark; Harvey L. Cromroy (EDIS)
The tropical fowl mite, commonly found on birds, has become a pest to man in areas of high bird populations or where birds are allowed to roost on roofs, around the eaves of homes, and office buildings. Nesting birds are the worst offenders. After the birds abandon their nests, the mites move into the building through windows, doors, and vents and bite the occupants. The bite is irritating to man and some individuals react to the bite with prolonged itching and painful dermatitis. Several to many reports are received each year of mites invading homes. The mites are usually the tropical fowl mite found in the central and southern areas of the state. The northern fowl mite, Ornithonyssus sylviarum (Canestrini and Fanzago), a close relative, is also found in Florida. This document is EENY-297 (originally published as DPI Entomology Circular 299), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2003.